An Exploration of Influencing Factors of Customer Relationship Management Practices in the Banking Sector - Kumari, Priyanka; Singh, Shivendra (Nepalese Journal of Management Science and Research, 2024)
The purpose of this study is to measure the deployment of customer relationship management (CRM), in the banking sector through the dimensions of CRM practices. The researcher implemented the Explorative Factor analysis (EFA) and factor scores to further segment the respondents’ descriptive statistical tools, such as frequency and percentage using SPSS V.21. The reliability of the questionnaire in this study was assessed using Cronbach’s Alpha. Multivariate regression has been used in this study to understand the correlation between CRM variables and customer satisfaction in the selected banking sector. Exploratory and descriptive study designs using a quantitative research approach were used to achieve the desired objective. A total of 176 samples were collected from respondents through surveys and interviews by the researcher to conduct the EFA test. The 20 scale items were used to evaluate the respondents’ opinions and four items interrelated to customer satisfaction regarding CRM practices in chosen banks. This study found that the CRM Practices measurement components of variables such as Customer Knowledge, Technology Orientation, Customer Value, Customer Trust, and Customer Retention are valid models and they have a significantly positive impact on customer satisfaction.